Social Guidance to Increase Solidarity between Employees of Different Religions - Amalia, Tasya; Mutiawati, Mutiawati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to find out how social guidance is carried out to increase solidarity among employees of PT Matahari Department Store Medan who have different religions. The method used is the qualitative case study method. Data collection techniques include observation, interviewing, and documentation. Data analysis is done through data reduction, presentation, and collection. The results show that social guidance to increase solidarity among fellow PT Matahari Department Store Medan employees is conducted through recitation and consecration. Recitation is carried out for Muslim employees and consecration for non-Muslim employees, where forms of solidarity are carried out by respecting and respecting fellow religions and those of different religions, not insulting friends of different religions, helping each other, and having a sense of caring and accepting input or opinions from other employees. This social guidance can foster a healthy and harmonious work environment and bring the company to its desired target.